Integrated optical sensors on the Si₃N₄-organic hybrid (SiNOH) platform - Kohler, Daria (Karlsruhe Series in Photonics & Communications, 2023)
A waveguide-based sensor chip is demonstrated that is suitable for point-of-care applications. The biosensor is designed using a mathematical model to investigate the sensitivity of the waveguides. A new class of integrated laser sources for visible wavelengths is being investigated for the first time for light coupling into the waveguides. The functionality of the waveguide-based biosensor chip is successfully demonstrated by detection experiments.